Energy efficiency in developing countries for the manufacuring sector - Cantore, Nicola (UNIDO ViennaAT, 2011)
Discusses the main findings coming out from the series of papers developed by the Overseas Development Institute (ODI) viz, that the most innovatiive firms show the lowest levels of energy intensity; that following a growth path where the level of energy per capita at a certain point endogenously decreases, without the need of specific energy reduction policies; that a lower level of energy intensity increases profitability; that there is an improvement in energy efficiency for those developing countries which show an economic structural change towards energy intensive manufacturing sectors during the growth path.